Enhancing community knowledge about the role of social capital on elderly’s well-being - Anung Ahadi Pradana; Renta Sianturi; Rohayati Rohayati (Community Empowerment, 2022)
The level of dependence of older adults increases with the increase in the life expectancy of older adults in the community. The role of the community as social capital can help older adults reduce the level of dependence to the caregivers and increase the independence of older adults in living their daily activity. The low level of community understanding regarding their role in increasing the level of independence of older adults is the reason for the need for providing information by professionals. The community empowerment is carried out online using zoom media with the aim to increasing public knowledge about the role of social capital in the health of older adults. The community empowerment was attended by 545 participants and discussed 10 main topics. The results of the activity showed significant positive benefits in changing one's cognitive status. This shows that the provision of health information to the public can bring positive benefits related to understanding the role of social capital on the health status of the elderly.